"EFFECTIVENESS OF LOCAL ANAESTHESIA (CLONIDINE AND FENTANYL) INFILTRATION FOR POST - NASAL SURGERIES." - Dr. Tejas Sambhaji Tambule,; Dr. Akash Sambhaji Tambule,; Dr. Gayatri Adinath Gathekar, (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Postoperative pain management following nasal surgeries is crucial for improving patient comfort and minimizing analgesic requirements. This study aimed to evaluate the effectiveness of local infiltration anesthesia combining clonidine and fentanyl in improving postoperative pain relief and overall comfort levels in patients undergoing nasal surgeries. The study compared this combination with standard infiltration anesthesia using lignocaine with adrenaline.Methods: A total of 60 patients undergoing nasal surgeries such as Functional Endoscopic Sinus Surgery (FESS), septoplasty, dacryocystorhinostomy, and nasal bone fracture reduction were enrolled in the study. Patients were randomized into two groups: the study group (n=30) received block anesthesia consisting of Inj. Lignocaine 2% (3ml), Inj. Lignocaine with Adrenaline 2% (3ml), Inj. Sensorcaine 0.5% (3ml), Inj. Fentanyl 50 µg/ml (0.5ml), and Inj. Clonidine 100 µg/ml (0.5ml); the control group (n=30) received infiltration anesthesia with Inj. Lignocaine with Adrenaline 2% (10ml). Discomfort levels were evaluated at 6 hours, 12 hours, Day 1, Day 2, and Day 7 postoperatively using predefined criteria: no discomfort, tolerable discomfort, and intolerable discomfort. Statistical analysis was performed using the Chi-square test.Results: Patients in the study group consistently experienced lower discomfort levels across all postoperative time points. At 6 hours, 30% of the study group reported no discomfort compared to only 15% in the control group (p